Comparison of brachial artery flow‐mediated dilation in youth with type 1 and type 2 diabetes mellitus. Issue 5 (26th February 2014) - Ohsugi, Koji; Sugawara, Hidenori; Ebina, Kanako; Shiga, Kentaro; Kikuchi, Nobuyuki; Mori, Masaaki; Yokota, Shumpei
Abstract Aims/Introduction Brachial artery flow‐mediated dilation (FMD) is a method of evaluating the function of vascular endothelial cells and is utilized for early diagnosis of atherosclerotic diseases. Only a few studies evaluated the risks for major vascular complications in youth with type 1 and 2 diabetes mellitus from the aspect of the early development of atherosclerosis. We studied whether there is a difference in vascular endothelial cell function between youth with type 1 and 2 diabetes mellitus. Materials and Methods We assessed %FMD of 24 patients with type 1 diabetes mellitus and 27 patients with type 2 diabetes mellitus aged 12–20 years along with glycated hemoglobin, lipid metabolism markers such as triglycerides, and inflammatory biomarkers such as total adiponectin levels in adolescent patients with type 1 or 2 diabetes mellitus. The significance of the difference in each factor between the type 1 and type 2 diabetes groups was assessed using Student's t‐test. Results The %FMD was significantly lower in patients with type 2 diabetes. The body mass index and blood pressure were significantly higher, and total and high‐molecular‐weight adiponectin levels were significantly lower in patients with type 2 diabetes. %FMD significantly correlated with systolic blood pressure. Conclusions The results suggest that youth with type 2 diabetes have more advanced damage of the vascular endothelium and therefore are at higher risk for major vascular complications. Therefore, monitoring the progression of atherosclerosis would also be beneficial in youth with diabetes mellitus, and measurement of FMD could be further warranted.